Effect of Light Intensity on the Biomass Production of Ceratophyllum demersum L. from Palm Oil Factory Treated Wastewater - Duera-oh, Usman; Kaosol, Thaniya (Princess of Naradhiwas University Journal, 2019)
This research aimed to study the effect of light intensity on the growth of Ceratophyllum demersum L. in the treated wastewater of the biogas system of palm oil factory. The comparison of the light intensity from the sun during the day time and the light intensity from artificial light of LEDs at 5,000 and 10,000 Lux during the night time on the algae cultivation was investigated, because the light intensity has an influence on the adsorption rate of nutrient which affects the growth of algae. The results showed that the increasing of light intensity affected the increasing of the cell operation in the biomass production. The algae cultivation experiment of light intensity from the sun during the day time and light intensity from an artificial light of LED at 10,000 Lux for algae cultivation in the treated wastewater which were diluted 10 times, was provided the best biomass production. Within four days, the biomass production was double and the growth rate of Ceratophyllum demersum L. was 8.17% per day of dry weight. At 18 days of Ceratophyllum demersum L. cultivation, These found that Ceratophyllum demersum L. cultivation can provide a good wastewater treatment in two weeks by reducing the total nitrogen and continually reducing the total phosphorus until the end of experiments with all dilution ratio of treated wastewater from palm oil factory.